Giant perivascular spaces: two case reports - Qi, Yuying; Han, Xiaofeng; Lu, Shujun; Ma, Wenbin; Chen, Panpan; Wang, Xuezhen (International Journal of Research in Medical Sciences, 2019)
Giant perivascular spaces or Virchow-Robin spaces (VRSs) are uniquely inherent developmental malformation and are generally lined by ependymal or leptomeningeal cells. The cerebral hemispheres with VRSs present multiple cysts of curvilinear, round, oval, or layered configuration, which have the same signal intensity as the cerebrospinal fluid (CSF) and represent extremely dilated VRSs. The cortex became extremely thin with a well-defined margin. Herein, we report two cases of true giant perivascular spaces and present a review of pertinent literature. A patient has multiple cysts in the unilateral and bilateral and has polycystic liver. The clinical presentation, image logical features, and diagnosis are discussed.